The new neighbor - Wilson, Carter (Novelist) (Poisoned Pen Press, 2022)
"Aidan Marlowe is the superstitious type--he's been playing the same lottery numbers for fifteen years, never hitting the jackpot. Until now. On the day of his wife's funeral. Aidan struggles to cope with these two sudden extremes: instant wealth beyond his imagination, and the loss of the only woman he's ever loved, the mother of his twin children. But the money gives him and his kids options they didn't have before. They can leave everything behind. They can start a new life in a new town. So they do. But a huge new house and all the money in the world can't replace what they've lost, and it's not long before Aidan realizes he's merely trading old demons for new ones. Because someone is watching him and his family very closely. Someone who knows exactly who they are, where they've come from, and what they're trying to hide. Someone who will stop at nothing to get what they want..."--